Speleothems of South American and Asian Monsoons Influenced by a Green Sahara. Issue 22 (13th November 2020) - Tabor, Clay; Otto‐Bliesner, Bette; Liu, Zhengyu
Abstract: The mid‐Holocene is frequently used for climate model‐proxy comparison studies, yet models often struggle to replicate the proxy signals from this period. Here, we use an Earth system model that tracks water isotopologies to determine the importance of a vegetated Sahara in the simulation of mid‐Holocene climate, with a focus on δ 18 O values recorded in speleothems from the South American and Asian monsoon regions. We find that inclusion of a vegetated Sahara during the mid‐Holocene leads to global warming and generally amplifies the changes in the δ 18 O values of the precipitation in the South American and Asian monsoon regions relative to preindustrial; both feedbacks improve model‐proxy agreement. Our results highlight the importance of regional vegetation alteration for accurate simulation of past climate, even when the region of study is far from the source of vegetation change. Plain Language Summary: The mid‐Holocene (6, 000 years ago) had slightly lower greenhouse gas concentrations and significantly higher Northern Hemisphere summer sunlight than preindustrial (1850 CE). There is also evidence for vegetation changes during the mid‐Holocene, most notably increased vegetation over the now arid Sahara. Most climate model simulations of the mid‐Holocene account for the greenhouse gas and orbital changes but frequently neglect the vegetation changes. Here, we use a climate model to separate the effects of a vegetated Sahara from those due to greenhouse gases and orbit during the mid‐Holocene. Our mid‐Holocene simulation with the addition of a vegetated Sahara better represents measurement‐based climate reconstructions of the period than our mid‐Holocene simulation that only includes greenhouse gas and orbital changes. These simulated improvements are particularly pronounced in the South American and Asian monsoon regions, despite their distance from the Sahara. Our results emphasize the importance of vegetation feedbacks when simulating past and future climate change. Key Points: Simulated mid‐Holocene with and without a Green Sahara using an Earth System Model that tracks water isotopologues A Green Sahara shifts the ITCZ north and amplifies changes in δ 18 O of precipitation in South America and Asia during the mid‐Holocene A Green Sahara leads to global warming and improves model‐proxy agreement in the low‐latitude monsoon regions during the mid‐Holocene